INFLUENCE OF WORKPLACE TECHNOLOGY ON SELECTED WORK VARIABLES IN NESTLESOCIETEANONYME AND NIGERIA BREWERY PLC., LAGOS, NIGERIA (2023)
Globally, workplace technology, the utilisation of equipment in organisations to execute tasks toincrease productivity and efficiency, has led to exponential revolution in work processes and hastremendously enhanced organisational productivity.InNigeria,particularly in food andbeverageindustry, technology has brought innovations with implications for work variables. Previous studies on workplace technology have focused on organisational productivity. However, scanty attention has been paid to the influence of workplace technology, especially on job satisfaction and commitment. This study investigated the levels of technology across workplace units and their influence on job skill, alienation, satisfaction and commitment in Nestle Societe Anonyme (S.A.)and Nigeria Brewery (NB) Plc., Lagos, Nigeria. Labour Process and Alienation theories provided a framework. A cross-sectional survey design was employed and data were collected using quantitative and qualitative approaches. Nestle S.A. and NB Plc., Lagos were purposively selected being the largest food and beverage conglomerates in Nigeria. Stratified sampling was used to select permanent staff across all cadres of both firms. A total of 447 respondents were drawn using Yamane’s (1967) sample size determination formula. Simple random sampling was used to proportionately administer questionnaire on 305 permanent staff in Nestle and 142 in NB. Thirty-eight (38) in-depth interviews were conducted with Units’ Heads: Nestle (18) NB (20). Burawoy’s (1985) model of classification of technological levels into low, medium and high was adopted. Quantitative data were analysed using descriptive statistics and One-way ANOVA at p≤0.05, while qualitative data were content-analysed. The respondents’ mean age was 32.41±1.0 years, 58.2% were males, 75.0% attained tertiary education in both organisations. Low technological level units: Nestle (3.2%) while NB (19.1%); medium technological level units: Nestle (71.7%) while NB (63.8%) and high technological level units: Nestle (25.0%) while NB (12.1%). Workplace technology differently influenced job skill across the three technological level units (low: 66.75, medium: 67.81 and high: 60.30) and was statistically significant in Nestle S.A.Workplace technology differently influenced job alienation across the three technological level units (low: 33.86, medium: 35.82 and high: 37.35) and was statistically insignificant in NB Plc. Workplace technology differently influenced job satisfaction across the three technological level units (low: 45.42, medium: 43.34 and high: 41.38) and was statistically significant in Nestle S.A. Workplace technology differently influenced job commitment across the three technological level units (low: 18.58, medium: 18.65 and high: 16.37) and was statistically significant in Nestle S.A.Technological transition decreased job skill. Departure from low-speed line to high-speed line and Information and Technology-support equipment decreased job alienation. Evolution of food and beverage analysers from manual to semi-automation and full-automation decreased job satisfaction and job commitment. Workplace technology decreased job skill, satisfaction and commitment in Nestle and Nigeria Brewery but alienation was not established in both organisations. Therefore, workers’ adaptation to the emerging challenges from workplace technology should be facilitated through capacity-building programmes.